2018
DOI: 10.1038/s41388-018-0488-5
|View full text |Cite|
|
Sign up to set email alerts
|

A molecular portrait of epithelial–mesenchymal plasticity in prostate cancer associated with clinical outcome

Abstract: The propensity of cancer cells to transition between epithelial and mesenchymal phenotypic states via the epithelial-mesenchymal transition (EMT) program can regulate metastatic processes, cancer progression, and treatment resistance. Transcriptional investigations using reversible models of EMT, revealed the mesenchymal-to-epithelial reverting transition (MErT) to be enriched in clinical samples of metastatic castrate resistant prostate cancer (mCRPC). From this enrichment, a metastasis-derived gene signature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(105 citation statements)
references
References 66 publications
4
95
0
Order By: Relevance
“…EMT involves a multitude of changes at both molecular and morphological levels. Various attempts to characterize the spectrum of EMT at molecular and/or morphological levels have been made recently, enabled by latest developments in multiplex imaging, single-cell RNA-seq and inducible systems (Mandal et al, 2016;Pastushenko et al, 2018;Stylianou et al, 2018;Cook and Vanderhyden, 2019;Devaraj and Bose, 2019;Karacosta et al, 2019;Wang et al, 2019b;Watanabe et al, 2019). These approaches have highlighted the dynamical nature of EMT in driving cancer progression in patients (Jolly and Celia-Terrassa, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…EMT involves a multitude of changes at both molecular and morphological levels. Various attempts to characterize the spectrum of EMT at molecular and/or morphological levels have been made recently, enabled by latest developments in multiplex imaging, single-cell RNA-seq and inducible systems (Mandal et al, 2016;Pastushenko et al, 2018;Stylianou et al, 2018;Cook and Vanderhyden, 2019;Devaraj and Bose, 2019;Karacosta et al, 2019;Wang et al, 2019b;Watanabe et al, 2019). These approaches have highlighted the dynamical nature of EMT in driving cancer progression in patients (Jolly and Celia-Terrassa, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that cancer cells can also stably exist in a hybrid epithelial-mesenchymal state wherein they co-express epithelial and mesenchymal markers Pastushenko et al, 2018). Cancer cells within a solid tumor exhibit widespread heterogeneity in the expression of epithelial and mesenchymal markers and can exhibit an epithelial (E), a mesenchymal (M), or one or more hybrid epithelial-mesenchymal (hybrid E / M) phenotype(s) (Hong et al, 2018;Kim et al, 2013;Pereira et al, 2015;Stylianou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Though the examples depicted are not complete, it is obvious that many nodes of this signaling network may participate in one or more mechanisms of cellular learning. Purple arrows highlight those nodes, which have already been identified as part of the mechanisms inducing epithelial-mesenchymal transition memory [44][45][46]. All of these nodes possess one or more features identified as potential mechanisms of cellular learning in our paper.…”
Section: Key Figurementioning
confidence: 80%
“…Several observations showed that epithelial-mesenchymal transition has a molecular memory [44][45][46]. Purple arrows in Figure 4 point to those nodes, which have already been identified as participants in these processes.…”
Section: Learning Of Signaling Networkmentioning
confidence: 93%